COVID-19 is a Conspiracy Disease? Diagnostic Mental Models and Students' Cognitive Abilities - Septaria, Kiki; Fatharani, Atika; Yasa, Arnelia Dwi (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2022)
Countless research has been published on the impact of covid-19 on improvements in teaching techniques, activities, and motivational beliefs. Most research refers to a human's response before learning without testing students' comprehension and literacy linked to covid-19. This study adopted a qualitative approach, with a questionnaire serving as the primary research tool. Alternatively, the current study looks into students' cognitive and portrays their mental model of COVID-19. At the Islamic University of Lamongan, 30 students from the science education department and 30 students from the environmental health department took part. Students are chosen as transformational leaders and liaisons between society's academic and social environments. The researchers gather data based on an open-ended assessment that evaluates the concepts, causation, methods, and strategies that must be implemented to prevent the transmission of COVID-19. Participants completed questionnaires prepared for educational purposes before and after learning. Inductive and iterative investigation of the descriptions of students' answers revealed cognitive outcomes and mental models. Each questionnaire form is then checked for validity using the SPSS v24 program. The authenticity of the questionnaire responses for each questionnaire > rcount (N = 60), indicating that each question is valid, whereas the reliability test using Cronbach's Alpha provides a score of 0.78 > 0.60, indicating that the questionnaire employed is trustworthy. Regarding educational, cognitive processes, the analysis shows that some colleagues believe that COVID-19 is a conspiracy, while others need to add sufficient scientific literacy to validate that COVID-19 is a disease. Even after learning, they can only make general ways to mitigate the propagation of COVID-19. The findings for student mental models revealed considerable changes in clarity and coherence, such as models at levels 1 through 5 with the highest student mental models. This study culminates with the implication that students require scientific literacy to effectively communicate about COVID-19 and check out false information in public.